LOST IN THE JURISDICTIONAL JUNGLE AND INTERPRETATIONAL MAZE: POWERS OF BANGLADESH COURTS IN RELATION TO FOREIGN SEATED ARBITRATIONS - Junayed Ahmed Chowdhury, (Journal of Malaysian and Comparative Law, 2023)
This article critically assesses the accuracy of the majority judgment in the latest case of Accom Travels and Tours Limited v Oman Air S.A.O.C before the High Court Division of the Supreme Court of Bangladesh with respect to the jurisdiction of Bangladesh courts in foreign seated arbitrations under the Arbitration Act (Act No. 1) 2001 (Bangladesh). The article argues that the majority judgment in Accom Travels and Tours Limited v Oman Air S.A.O.C lost sight of the jurisdictional parameters of the court and the related interpretational elements under the Arbitration Act (Act No. 1) 2001 (Bangladesh) in relation to foreign seated arbitrations in the light of comparable judgments of India, United Kingdom and the United States of America.